Integrative osmotic–antioxidant mechanisms in salinity-stressed Gerbera jamesonii treated with proline–IAA and PGPR - Karagüzel, Ümmü Özgül (Frontiers in Plant Science, 2026)
Salinity stress is a major abiotic constraint that adversely affects the productivity and ornamental value of Gerbera jamesonii Bolus ex Hook. f. This study evaluated the physiological and biochemical responses of two cultivars (‘Zingana’ and ‘Sene Vidi’) to NaCl-induced salinity and examined the mitigation potential of microbial and biostimulant applications. Plants were subjected to six treatments under controlled greenhouse conditions: Control, NaCl, NaCl + Bacteria, NaCl + Proline–IAA, Bacteria, and Proline–IAA. Salinity markedly reduced relative water content (RWC), chlorophyll pigments, and leaf area, while increasing lipid peroxidation (MDA), indicating oxidative and osmotic stress. The bacterial and Proline–IAA treatments, applied either alone or under salinity, alleviated these negative effects by maintaining water status, stabilizing pigments, and lowering MDA levels. The Proline–IAA biostimulant, in particular, enhanced osmotic regulation and chlorophyll preservation, while bacterial inoculation improved overall physiological resilience. Principal component and correlation analyses revealed strong positive associations among RWC, chlorophyll content, and leaf area, whereas MDA was negatively correlated with growth parameters. Overall, both microbial and Proline–IAA applications improved the salinity tolerance of G. jamesonii, supporting their use as sustainable tools for maintaining growth performance and ornamental quality under saline conditions.